2018
DOI: 10.14196/mjiri.32.8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of food addiction among Iranian children and adolescents: Associations with sociodemographic and anthropometric indices

Abstract: Background: Food addiction has been defined as consuming palatable foods leading to addictive-like behaviors. Little studies have assayed food addiction in children and adolescents. Thus, we aimed at identifying the prevalence of food addiction and the relationship between food addiction, sociodemographic and anthropometric indicators among children and adolescents in southwestern Iran. Methods: This cross-sectional study was conducted on 222 elementary school students aged 7 to 13 years in Ahvaz, Iran, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(75 reference statements)
3
8
0
3
Order By: Relevance
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of FA as determined using the YFAS‐C has been reported in 18 publications 24,28–32,34–39,41,42,45–48 (Table 2). The meta‐analysis estimated an overall FA prevalence at 15% (95% CI: 11–19%) among children and adolescents, with an I 2 of 95.64%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the prevalence of FA in different populations using the criteria for substance dependence in the DSM-IV [e.g., [6][7][8]11]. Moreover, Gearhardt et al [9] developed the Yale Food Addiction Scale (YFAS) for assessing FA based on the diagnostic criteria for substance dependence in the DSM-IV.…”
Section: Introductionmentioning
confidence: 99%
“…A major reason for the dearth of FA studies among Persian-speaking children and adolescents is the lack of a validated instrument for usage. Although one recent Iranian study translated the YFAS-C and applied the Persian YFAS-C to 222 elementary school students to assess FA [ 11 ], the study did not provide any psychometric evidence for the robustness translated YFAS-C. Researchers and healthcare providers may, therefore, hesitate to use the Persian YFAS-C because the psychometric properties are not known.…”
Section: Introductionmentioning
confidence: 99%